PENGARUH VISUAL KEMASAN PADA PRODUK PRIVATE LABEL MINIMARKET ALFAMART TERHADAP KEPUTUSAN PEMBELIAN - Vera Vellina; Adi Nugroho (Jurnal Titik Imaji, 2020)
This research focuses on analyzing the packaging's visual of a private label product issued by Alfamart minimart. Minimart is one of the retail space classification level based on standards applied worldwide and also adopted in Indonesia. Alfamart brand is chosen because they got the Top Brand award by SWA Magazine and Brand Finance Indonesia in 2017. In today's competitive market, big retailers invent many innovative strategies to maintain their existence and brand domination. One of the strategy is to issue private label products (products which are produced using the retailer's own brand and packaging). This strategy initially started in Europe since 1976 by a French big retailer Carrefour (Bozhinova, 2013). After that, it is then adopted by retailers in other parts of Europe and the world. Indonesia also starts to implement this strategy at the start of the global economy era on 1990-2000. Indonesian local retailers also adopt the private label strategy as part of their product development, brand awareness, and sales. Private product label in Indonesia is somewhat special because the products are not produced by themselves, but bought from small businesses which then rebranded using their own label. The case study used in this research is the packaging of Alfamart's facial tissue commonly used by females. This product is one of the biggest segment in Indonesian's retail market. This research is using combined method of literature study and Focus Group Discussion (FGD) using purposive sampling method. The FGD results will then be analyzed and could serve as development materials for further research in retail, visual communication, marketing, and design field. In the long run, this research can give benefits for retail owners and small business owners who want to sell their own product apart from the network of big retailers.